PENGARUH PROFITABILITAS DIVIDEND PAYOUT RATIO TERHADAP RETURN SAHAM: Perusahaan Subsektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2015 – 2021 - Eka Sutisna; Edi Suhara; Ai Rastini; Dheila Ziehandiny (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The purpose of this study was to determine the effect of profitability and dividend payout ratio on stock returns in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2021. The population used in this study were 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). While the samples taken were 6 companies in the food and beverage sub-sector using purposive sampling technique. Data collection techniques using documentation techniques. The results showed that simultaneously profitability and Dividend Payout Ratio (DPR) had no effect on stock returns. Partially, the profitability variable has a negative and significant effect on stock returns and the Dividend Payout Ratio (DPR) has a negative and significant effect on stock returns